A Rare Case of Chronic Suppurative Appendicitis in Neonatal Presenting as Intestinal Malrotation - Pradnyanita Mustika, Putu; Sukmawati, Made; Darmajaya, I. Made; Dewi, I. G. A. Sri Mahendra; Artana, I. Wayan Dharma; Kardana, Made; Putra, Putu Junara; Ariyanta, Kadek Deddy (Open Access Macedonian Journal of Medical Sciences, 2021)
Neonatal appendicitis (NA) is an extremely rare acute abdomen condition, moreover, if it is a chronic suppurative one. The definite risk factor of NA is barely unknown. The signs and symptoms are often nonspecific and appear after perforation occurs. Most of the cases were found unexpectedly during surgery suspected as other diagnoses. A 7-day-old male neonate presenting lethargic and hypoglycemia since 1 st day of life. Patient drunk breast milk right after since he was born. Meconium was produced <24 h. On the 3 rd day of hospitalization, he experienced bilious vomiting and abdominal distension, so nasogastric tube was installed. Physical examination revealed decreased bowel sound. Investigation showed leucocytosis, slightly increased procalcitonin and abdominal X-ray showed that gas distribution lasted until third part of duodenum followed by minimal gas distribution in the distal part of duodenum. The patient was suspected as distal duodenum stenosis or proximal jejunum. Intraoperatively, it was found that there was second part duodenum malrotation and open Ladd’s procedure was done. During Ladd’s procedure, a perforated appendix was also found. The histopathology result revealed that it was a chronic suppurative appendicitis. Patient was discharged in good condition 20 days after surgery. NA is a rare condition with nonspecific signs and symptoms which was usually found accidentally during surgery suspected as other diagnoses.